Shopbots, powershopping, powersales: New forms of intermediation in E-Commerce. An overview - Astrid Meck (Universität Augsburg, Institut für Volkswirtschaftslehre, 2001)
With the advent and proliferation of the Internet many aspects of business and market activities are changing. New forms of intermediation also called cybermediaries are becoming increasingly important as a coordinator of interaction between buyers and sellers in the electronic market environment. Especially the overwhelming abundance of information offered by the Internet promotes the development of new intermediarie like malls, shopbots, virtual resellers etc. This paper provides a detailed overview of different new forms of cybermediation and illustrates their influence on consumer choice, firm pricing and product differentiation strategies.
urn:nbn:de:bvb:384-opus4-712608
Keywords: L81; 330; comparison shopping; cybermediaries; e-commerce; shopbots